Using an epidemiological framework and bovine spongiform encephalopathy investigation questionnaire to investigate suspect bovine spongiform encephalopathy cases: an example from a bovine spongiform encephalopathy case in Ireland in 2015. (10th February 2018) - O'Connor, Jarlath T; Byrne, Justin P; More, Simon J; Blake, Martin; McGrath, Guy; Tratalos, Jamie A; McElroy, Maire C; Kiernan, Paul; Canty, Mary J; O'Brien‐Lynch, Chris; Griffin, John M
Abstract : In several EU member states, bovine spongiform encephalopathy (BSE) cases have been identified in cattle born after the reinforced ban (BARB cases), for reasons that are not entirely clear. Epidemiological investigation of these cases has proved challenging. The European Food Safety Authority recently recommended the collection of a predefined set of epidemiological data from BSE suspects and confirmed BSE cases to aid future investigations. In this study, we present an epidemiological framework and BSE investigation questionnaire to aid the investigation of suspect BSE cases, and illustrate its application during the investigation of a BSE case in Ireland in 2015. It is recommended that the framework and questionnaire are used concurrently: the framework provides structure and focus, whereas the questionnaire (with 135 questions) aids data collection. The framework focuses on confirmation and discrimination, estimating the date and location of exposure, and determining the method/source of exposure. The BSE case in Ireland in 2015 was a BARB case born in 2010. It was identified with classical BSE at an authorised knackery as part of Ireland's targeted active surveillance programme for BSE. No definitive source of infection with the BSE agent could be attributed in this case.